PENGGUNAAN METODE PERAMALAN DALAM PRODUKSI KAYU UNTUK PENENTUAN TOTAL PERMINTAAN (KONSUMEN) - Widiyarini Widiyarini (Universitas Indraprasta PGRI, 2016)
A manufacturer that runs on timber manufacturing industry do a forecast about consumer demand about albasia bare core product. The selling forecast of thirteen milimeters, fifteen milimeters, and sixteen milimeters bare core obtained from the past selling data, then the data processed with double moving average and double exponential smooting forecast method. With mean absolute percentage error (MAPE) method, the percentage of smallest error could be found. The result of forecast that will be used for the production plan for thirteen milimeters thickness bare core is using double exponential smooting method zero point five with one point nine one of MAPE, then fifteen milimeters thickness bare core is using double exponential smooting method zero point five with one point seven zero of MAPE, and sixteen milimeters thickness bare core is using double exponential smooting method zero point five with one pont zero three eight of MAPE. Keywords: forecasting, double moving average, double eksponential smoothing